2003
DOI: 10.1038/sj.ijo.0802528
|View full text |Cite
|
Sign up to set email alerts
|

Excess accumulation of body fat is related to dyslipidemia in normal-weight subjects

Abstract: OBJECTIVE: To assess the relationship of fat mass (FM) and its distribution to hypertension and dyslipidemia in normal-weight Japanese individuals. DESIGN: Cross-sectional study. SUBJECTS: Apparently healthy Japanese subjects with a body mass index (BMI) between 20 and 23.5 kg/m 2 (265 males and 741 females, age 21-69 y). MEASUREMENTS: BMI, waist circumference (WC), waist-hip ratio (WHR), systolic and diastolic blood pressure, serum levels of total cholesterol (TC), high-density lipoprotein-cholesterol (HDL-C)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
2
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 28 publications
3
50
2
2
Order By: Relevance
“…Waist circumference (WC) and waist-hip ratio have been widely used as simple and inexpensive indices for screening one's fat distribution [1][2][3][4]. Although the assumption that WC reflects trunk fat mass (FM) or visceral FM is relatively straightforward [5][6][7], the significance of hip circumference (HC) is not clear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Waist circumference (WC) and waist-hip ratio have been widely used as simple and inexpensive indices for screening one's fat distribution [1][2][3][4]. Although the assumption that WC reflects trunk fat mass (FM) or visceral FM is relatively straightforward [5][6][7], the significance of hip circumference (HC) is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Amongst them, 4256 subjects (1249 men and 3007 women, age 20-79 years) were analysed in the present study. Part of the subjects has been analysed in our previous studies [4,17,19]. Those with a history of cardiac, pulmonary, renal or malignant disease and those who were currently taking medications were excluded from the study.…”
Section: Subjectsmentioning
confidence: 99%
“…However, the degree of obesity is not necessarily correlated with the severity and frequency of such disorders. Ito et al (1) reported that excess accumulation of fat mass, especially in the upper body, was related to dyslipidemia in normal-weight Japanese individuals. Moreover, intra-abdominal adiposity has been found to be associated with glucose intolerance, elevated triglyceride (TG), low HDL cholesterol (HDL-C) levels, and hypertension in both clinical (2) and population-based prospective cohort studies (3).…”
Section: Introductionmentioning
confidence: 99%
“…Alternative noninvasive methods to quantify regional adiposity have been used in clinical and epidemiological studies. The use of waist-to-hip ratio (WHR) or waist circumference (1), and abdominal fat deposition by ultrasonography (6,(7)(8)(9) as predictors of atherosclerotic risk have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…As concentrações de CT, triglicerídeos e LDL correlacionam-se positivamente com a gordura corporal, enquanto as de HDL, negativamente 12 , sendo que indivíduos com sobrepeso e obesidade apresentam maiores concentrações de triglicerídeos, LDL e CT 13 . Ademais, o acúmulo excessivo de gordura corporal está associado à presença de dislipidemias 14 . Somado a isso, o excesso de adiposidade corporal acomete uma parcela significativa da população, haja vista que, em torno de 47,8% das crianças, 25,4% dos adolescentes e 63,8% dos adultos 15 encontram-se em estado de sobrepeso/obesidade.…”
Section: Introductionunclassified